Correlation Between Bowel Preparation and the Adenoma Detection Rate in Screening Colonoscopy - Park, Jung Hun (Ann Coloproctol, 2017)
PURPOSE: The adenoma detection rate is commonly used as a measure of the quality of colonoscopy. This study assessed both the association between the adenoma detection rate and the quality of bowel preparation and the risk factors associated with the adenoma detection rate in screening colonoscopy. METHODS: This retrospective analysis involved 1,079 individuals who underwent screening colonoscopy at the National Cancer Center between December 2012 and April 2014. Bowel preparation was classified by using the Aronchick scale. Individuals with inadequate bowel preparations (n = 47, 4.4%) were excluded because additional bowel preparation was needed. The results of 1,032 colonoscopies were included in the analysis. RESULTS: The subjects' mean age was 53.1 years, and 657 subjects (63.7%) were men. The mean cecal intubation time was 6.7 minutes, and the mean withdrawal time was 8.7 minutes. The adenoma and polyp detection rates were 28.1% and 41.8%, respectively. The polyp, adenoma, and advanced adenoma detection rates did not correlate with the quality of bowel preparation. The multivariate analysis showed age ≥ 60 years (hazard ratio [HR], 1.42; 95% confidence interval [CI], 1.02–1.97; P = 0.040), body mass index ≥ 25 kg/m(2) (HR, 1.56; 95% CI, 1.17–2.08; P = 0.002) and current smoking (HR, 1.44; 95% CI, 1.01–2.06; P = 0.014) to be independent risk factors for adenoma detection. CONCLUSION: The adenoma detection rate was unrelated to the quality of bowel preparation for screening colonoscopy. Older age, obesity, and smoking were independent risk factors for adenoma detection.